The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5585/riae.v13i1.1884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of University-Industry Interaction on Firm’s Innovation: Empirical Evidence from Brazilian Firms.

Abstract: Este trabalho investiga a interação universidade-indústria e seus efeitos sobre a probabilidade de inovação de produtos e processos em um país em desenvolvimento. Especificamente, discute-se que as empresas diferem em tipos e aspectos determinantes para interagir com as universidades e estas diferenças podem proporcionar resultados de inovação distintos. Coletamos e analisamos dados primários de 325 companhias que possuíam alguma interação com universidades em anos anteriores. Os resultados de regressão logíst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…In addition to the studies that have shown a positive correlation between variables observed in this article, there are studies that failed to prove such a positive correlation (Laursen & Salter, 2004;Radas, 2005;Medda, Piga, & Siegel, 2006;Puffal & Teixeira, 2014;Jaklič, Damijan, Rojec, & Kunčič, 2014). For instance, while assessing the commercial value of academic output, Klevorick, Levin, Nelson, and Winter (1995) determined that the direct influence of academic research on innovativeness of companies is very low compared to other sources of funding.…”
Section: Literature Reviewmentioning
confidence: 77%
“…In addition to the studies that have shown a positive correlation between variables observed in this article, there are studies that failed to prove such a positive correlation (Laursen & Salter, 2004;Radas, 2005;Medda, Piga, & Siegel, 2006;Puffal & Teixeira, 2014;Jaklič, Damijan, Rojec, & Kunčič, 2014). For instance, while assessing the commercial value of academic output, Klevorick, Levin, Nelson, and Winter (1995) determined that the direct influence of academic research on innovativeness of companies is very low compared to other sources of funding.…”
Section: Literature Reviewmentioning
confidence: 77%
“…This finding is consistent with the results of many other studies. [ 33 34 35 ] Meanwhile, the industry and university participation proposes a special capacity to organizational innovation capability. [ 33 34 35 36 ] Organizational climate is created by the collective experience of people from their work environment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 34 35 ] Meanwhile, the industry and university participation proposes a special capacity to organizational innovation capability. [ 33 34 35 36 ] Organizational climate is created by the collective experience of people from their work environment. [ 37 38 39 ] The study findings are also indicative of the innovative climate on the organizational innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Neste modelo, a essência de um SNI é a construção de uma base de conhecimentos que ocorre por meio das interações entre os sistemas político e operacional. Assim, os recursos para a criação de uma base de conhecimento não envolvem apenas as atividades de P&D, novos produtos e processos, mas também vêm da estrutura produtiva (NACLERIO, 2010 (PUFFAL, 2015), ou estão relacionados à aplicação de tecnologias desenvolvidas por setores de intensidade tecnológica elevada Smith, 2005). Por conseguinte, a baixa geração de patentes não implica necessariamente em taxa igualmente baixa de geração de inovações nos países analisados.…”
unclassified